Prospects of Agricultural Land Use Formation in the Conditions of Introduction of Agricultural Land Market in Ukraine - Kolisnyk, H.; Trokhymenko, I. (Land Management, Cadastre and Land Monitoring, 2021)
The evolution of agricultural land use development in Ukraine has been studied. The main factors influencing the land market on the formation of agricultural land use are identified, they include: the number of potential buyers (land users) and sellers, the expiration of the lease agreement, the structure of the land bank of the agricultural enterprise (lease, ownership), land consolidation based on land purchase and sale . The article, based on the example of Narizhanska village council of Poltava region, established that only 30 percent of landowners will be able to sell their land plots in the first 2 years due to the expiring lease agreement.The authors study the factors influencing the efficiency of agricultural land use in the land market, the main ones are: disruption of crop rotation, excessive agricultural development and plowing, low rents and competition of land users, a small number of small land uses with poor financial stability, destructive changes -climatic conditions, lack of effective tools for termination of lease agreements, lack, to a large extent, of information on territorial restrictions in the State Land Cadastre and more.The article proposes to make proposals to the regulatory framework in terms of the possibility of one-time termination or re-conclusion of lease agreements due to changes in significant conditions (turnover of agricultural land), which will intensify the sale process, increase investment attractiveness of agricultural land use by increasing the portfolio private property, land consolidation, simplification of the land exchange process, involvement of a larger share of credit and financial institutions in the formation of land use, as well as positively affect the welfare of landowners (shares) and more.The article proposes to ensure the formation of sustainable land use by improving the regulatory framework, ensuring an environmentally friendly structure of sown areas primarily through strengthening the role of landowners, increasing the share of small or medium agricultural land use.Keywords: agricultural land use, agricultural land market, land lease, landowners, land users